Impact of Technology Use on Behavior and Sleep Scores in Preschool Children in Saudi Arabia - Almuaigel, Doaa; Alanazi, Abrar; Almuaigel, Mohammed; Alshamrani, Foziah; AlSheikh, Mona; Almuhana, Nora; Zeeshan, Mohammad; Alshurem, Mohammed; Alshammari, Alaa; Mansi, Kamel (Frontiers in Psychiatry, 2021)
Background: Pre-school children use digital technologies both at home and in kindergarten for communication. However, such technologies can also be used for creativity and entertainment. Technology usage might exert a negative impact on the health and psychosocial development of pre-school children, thus necessitating parental monitoring to control the negative effects. Early intervention for pre-school children, decrease in the duration of technology use, spending more time with family, and participation in motor activities recommended order to decrease the impact on behavior and sleep disturbance. Aim: To investigate the perception of parents toward the negative health, behavioral, and sleep consequences of technology usage by children in Saudi Arabia (SA). Method: This cross-sectional study was conducted across two regions in SA. It was ethically approved by the ethical review board of Imam Abdulrahman Bin Faisal University. The participants were randomly selected and interviewed to obtain data for the following measures: demographic and clinical data, technology usage, sleep disturbance scale for children, and children's behavior questionnaire in which higher the score, more sleep and behavior problems problem. We excluded children with comorbidities from the study. Results: We recruited 288 children. Most did not attend schools (63.2%), while 22.6% were in kindergarten, and 14.2% were in nursery schools. Smart phones were the most commonly used devices by the children (42.4%). Furthermore, most used the technology for 2–3 h/day (34%). Cartoons were the most commonly sought content (42%). The behavior scores for children aged 18 to 36 months showed a mean value of 5.1, 3.7, and 4.6 for surgency, negative affect, and effortful control, respectively. In contrast, children aged 3 to 5 years showed a mean value of 4.3, 4, and 4.7 for surgency, negative affect, and effortful control, respectively. Sleep disturbance scores for all children showed a mean value of 12.4, 3.5, 3.8, 8, 7.3, and 2.7 on disorders of initiating and maintaining sleep, sleep-breathing disorders, disorders of arousal, sleep-wake transition disorders, disorders of excessive somnolence, and sleep hyperhidrosis, respectively. The mean total score was 37. Conclusion: In conclusion, technology use might exert a negative impact on children by disturbing their sleep and behavior.